Fast frequency response of inverter-based resources and its impact on system frequency characteristics - Lining Su; Xiaohui Qin; Shang Zhang; Yantao Zhang; Yilang Jiang; Yi Han (Global Energy Interconnection, 2020)
The inertia response and primary frequency regulation capability of synchronous grids are declining owing to the increasing penetration of inverter-based resources. The fast frequency response (FFR) of inverter-based resources is an important mitigation option for maintaining grid security under the conditions of low inertia and insufficient primary frequency response capability. However, the understanding and technical characteristics of the FFR of inverter-based resources are still unclear. Aiming at solving the aforementioned problems, this paper proposes a definition for FFR based on the impact mechanism of FFR on system frequency. The performance requirements of FFR are clarified. Then, the effects of FFR on system frequency characteristics are further analyzed based on steady-state frequency deviation, the initial rate of change of frequency, and the maximum transient frequency deviation. Finally, the system requirements for FFR and its application effects are verified by simulating an actual bulk power grid, providing technical support for subsequent engineering application.